2006
DOI: 10.1080/00379271.2006.10697483
|View full text |Cite
|
Sign up to set email alerts
|

Yield loss due to the stemborerChilo partellus(Swinhoe) (Lepidoptera: Crambidae) at different nitrogen application rates to maize

Abstract: Abstract. Field trials were conducted at Kibaha and Morogoro in eastern Tanzania during two seasons to evaluate the effect of nitrogen fertilization (0, 50, 75, 100 kg [N]/ha) on pest abundance, plant damage and yield loss of maize due to stemborers. In general, ear and grain weights increased linearly with nitrogen level. In the infested plot, grain weight increased 2.5 and 1.8 fold from 0 to 100 kg [N]/ha in the short and long rainy season, respectively, at Kibaha, and 1.4 and 1.6 times at Morogoro. Yield lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 19 publications
1
13
1
Order By: Relevance
“…Improving soil fertility complements pest control measures (Saroja et al, 1987). Various authors Chabi-Olaye, 2005;Mgoo et al, 2006;Wale et al, 2006a) have shown that nitrogen is associated with the survival of young stemborer larvae and the resulting pest infestation as well as the plants' tolerance to subsequent attacks. Furthermore, reports from western Africa show that the nutritional status of maize affects noctuid borer densities and the ability of the plants to compensate for pest damage.…”
Section: Introductionmentioning
confidence: 99%
“…Improving soil fertility complements pest control measures (Saroja et al, 1987). Various authors Chabi-Olaye, 2005;Mgoo et al, 2006;Wale et al, 2006a) have shown that nitrogen is associated with the survival of young stemborer larvae and the resulting pest infestation as well as the plants' tolerance to subsequent attacks. Furthermore, reports from western Africa show that the nutritional status of maize affects noctuid borer densities and the ability of the plants to compensate for pest damage.…”
Section: Introductionmentioning
confidence: 99%
“…Limited stem borer losses by farmers using fertilizers even under stem borer attack could suggest a suppression effect of fertilizers on stem borer damage. Such effects were reported by [27] who showed reduced yield losses due to stem borers in maize with increased use of nitrogen fertilizer. However, our data also indicates that high-input users do not only use high amounts of fertilizers, but also other inputs such as pesticides and improved seed.…”
Section: Survey Resultsmentioning
confidence: 72%
“…In the case of stem borer resistant hybrids, the higher pesticide use resulted in actual savings when changing to GM maize resistant to stem borers. Further advantages could result from the loss-reducing effect fertilizer can have on stem borer infestations in maize fields as evidenced by earlier studies that reported reduced damage of stem borers with increase in nitrogen fertilizer application [27,36]. Faster adoption of GM technology by advanced farmers was also described by Gouse et al [29] who reported earlier adoption of Bt maize for farmers who had previously used hybrid seed in South Africa.…”
Section: Partial Budget Analysismentioning
confidence: 70%
“…high N, P and organic carbon. A similar study carried out in Tanzania showed that yield losses linearly decreased with an increase in N level (Mgoo 2005).…”
Section: Discussionmentioning
confidence: 84%
“…1995; Chabi‐Olaye et al. 2005a; Mgoo 2005) nitrogen not only enhances survival of young stemborer larvae and thereby pest infestations but it also enhances the plant's tolerance to stemborer attacks. Reports from western Africa show that the nutritional status of maize affects noctuid borer densities as well as the plant's ability to compensate for pest damage.…”
Section: Introductionmentioning
confidence: 99%